"The Times Do Not Permit": Moerane, South Africa, Lesotho, and Fatše La Heso. Issue 2 (3rd July 2019) - Lucia, Christine
Abstract: The symphonic poem Fatše La Heso (My Country) was composed in 1941 by Michael Mosoeu Moerane (1904–1980) as a requirement for completing a BMus degree curriculum through Rhodes University College, which in those days was a satellite campus of the University of South Africa (Unisa). This article argues that both the writing of this work and its subsequent reception history have been adversely affected by various factors, beginning with the fact that Moerane was the first black South African orchestral composer and there have been almost no others since. This was Moerane's only work for full orchestra and he is better known as a composer of choral music in tonic solfa notation, but for historical reasons, the fields of African choral and European orchestral composition have not coincided. The work reflects Moerane's Pan- African sympathies and is avowedly nationalistic. Information about the work and about Moerane has always been scant; and finally, Moerane tried in vain to get the work published. He reacted suspiciously when Percival Kirby—with whom he had previously corresponded about the work—began to ask him personal questions in 1966, saying, "The times do not permit." In this article, the genesis of Fatše La Heso is explained, its structure and relations to African themes are described, and its reception history is explored, in order to promote a better and fairer understanding of this work's personal, historical, political, and cultural significance.